KARYA-KARYA KITAB ULAMA DI PONDOK PESANTREN SEBERANG KOTA JAMBI - Puji Rahayu, Alif; Gunawan, Hendra; Zami, Rahyu (Borneo : Journal of Islamic Studies, 2024)
This research examines the books written by Islamic scholars in Islamic boarding schools throughout Jambi City, which serve as teaching materials for efforts to preserve the nation's cultural heritage. We conduct field research using historical methods. This study can be presented with data obtained through field research. According to the data collection, quite a few Ulama works have been discovered. The Pondok communThe Pondok community demonstrates a strong commitment to safeguarding these works, as evidenced by their continued preservation of the ulama's originTo date, some of these works have been reprinted for study and distribution.